2007
DOI: 10.1097/brs.0b013e31814b2d3c
|View full text |Cite
|
Sign up to set email alerts
|

Complications in Posterior Fusion and Instrumentation for Degenerative Lumbar Scoliosis

Abstract: The complication rate after posterior fusion and instrumentation for degenerative lumbar scoliosis was 68%. Abundant blood loss was a significant risk factor for early perioperative complications. The improvement of Oswestry disability index was less in patients with late complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
195
2
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(212 citation statements)
references
References 15 publications
6
195
2
3
Order By: Relevance
“…First, it has been reported that fusion surgery for DLS has a relatively high complication rate than for other degenerative diseases such as spondylolisthesis [2,4,19]. Therefore, for patients who are poor candidates for massive spinal reconstruction surgery because of their general condition, our decompression technique is a treatment option.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it has been reported that fusion surgery for DLS has a relatively high complication rate than for other degenerative diseases such as spondylolisthesis [2,4,19]. Therefore, for patients who are poor candidates for massive spinal reconstruction surgery because of their general condition, our decompression technique is a treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…With development in spinal instrumentation, fusion surgery is preferred, especially in patients with degenerative lumbar scoliosis (DLS) due to malalignment and instability. However, fusion surgery poses problems, such as adjacent segment disease and pseudoarthrosis [2,4,19]. Because patients with DLS are often elderly, surgical invasion and instrumentation failure due to osteoporosis also create problems in fusion surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Studies highlighted that complications remain a common occurrence and a significant concern in adult scoliosis surgery, with rates ranging from 10 to 40 % on middle-age adults and higher in the elderly patients. Despite the high complication rates, recent evidence demonstrates the potential benefits of surgical treatment for adult scoliosis, reporting a significant improvement of the outcome measures as compared with baseline measures [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have documented the complications of these surgical techniques [1,5,11,23,30]. The reported rates of complications in One of the authors (AAP) owns stock in Amedica (Salt Lake City, UT), Nocimed (Redwood City, CA), and Cytonics (Jupiter, FL); consults for Amedica, Biomet (Warsaw, IN), and Stryker Spine (Kalamazoo, MI); receives royalties from Amedica; and has received research funding from Stryker Spine through his institution.…”
Section: Introductionmentioning
confidence: 99%
“…Anteriorapproach complications include damage to the abdominal organs (\ 1%), vascular injury (1.3%-15.6%), disruption of the sympathetic plexus (1.7%-13.3%), and postoperative ileus (0.6%-5.6%) [6,[29][30][31]. Posterior approaches avoid the aforementioned risks but can lead to soft tissue devitalization, nerve root injuries (9%-16%), postoperative radiculitis (6.7%-16.4%), and incidental durotomies (5.4%-10%) [5,9,26,31]. Newer surgical techniques were developed in hopes of minimizing surgical risks, decreasing in-hospital stay, and potentially improving patient satisfaction [17].…”
Section: Introductionmentioning
confidence: 99%